Color-coded parametric imaging support display of vessel hemorrhage—an in vitro experiment and clinical validation study - Chen, Yi; Xu, Wenji; Liu, Jiaxin; Zhao, Chao; Cao, Xiaojing; Wang, Rong; Feng, Duiping; Zhang, Ruiping; Zhou, Xiang (Frontiers in Cardiovascular Medicine, 2024)
Background：Digital Subtraction Angiography (DSA) is currently the most effective diagnostic method for vascular diseases, but it is still subject to various factors, resulting in uncertain diagnosis. Therefore, a new technology is needed to help clinical doctors improve diagnostic accuracy and efficiency. Purpose: The objective of the study was to investigate the effect of utilizing color-coded parametric imaging techniques on the accuracy of identifying active bleeding through DSA, the widely accepted standard for diagnosing vascular disorders. Methods: Several variables can delay the diagnosis and treatment of active bleeding with DSA. To resolve this, we carried out an in vitro simulation experiment to simulate vascular hemorrhage and utilized five color-coded parameters (area under curve, time to peak, time-of-arrival, transit time, and flow rate of contrast agent) to determine the optimal color coding parameters. We then verified it in a clinical study. Results: Five different color-coded parametric imaging methods were compared and the time-of-arrival color coding was the most efficient technique for diagnosing active hemorrhage, with a statistically significant advantage (P<0.001). In clinical study, 135 patients (101 with confirmed bleeding and 34 with confirmed no bleeding) were collected. For patients whose bleeding could not be determined using DSA alone (55/101) and whose no bleeding could not be diagnosed by DSA alone(35/55), the combination of time-of-arrival color parametric imaging was helpful for diagnosis, with a statistically significant difference (P<0.01 and P=0.01). Conclusions: The time-of-arrival color coding imaging method is a valuable tool for detecting active bleeding. When combined with DSA, it improves the visual representation of active hemorrhage and improves the efficiency of diagnosis.